An Analysis on the Sources of Developmental Information among the People of Mambilla, Sardauna Local Government Area of Taraba State - Isa, Jibril G.; Oliver, Mary Ntala (International Journal of Humanities, Education, and Social Sciences, 2024)
People of the Mambilla Plateau in Taraba State's Sarduana Local Government Area are believed to be cut off from the rest of the state due to a poor road network, a lack of internet connection in some regions, and a lack of active traditional media presence. On light of the above, this study adopted the survey method to explore the sources of development messages on the Mambilla Plateau. Findings of this study revealed the major sources of developmental information among the populace of the Mambilla Plateau in Sardauna Local Governemnt Area of Taraba State include religions institutions such as Mosques and Churches and traditional leaders. Results of this study also revealed that some of the factors militating against access to developmental information among the populace of the Mambilla Plateau in Sardauna Local Government include lack or absence of the conventional media such radio, television and newspaper; poor road network, illiteracy and language barrier. Therefore the study recommended among other things that there is the need for the government and stakeholders to ensure the active presence of the conventional media outfits on the Mambilla Plateau.]